Gold–Mercury–Platinum Alloy for Light-Enhanced Electrochemical Detection of Hydrogen Peroxide - Yunping Wei; Runze Li; Meng Lin (Sensors)
In this study, a simple and easy synthesis strategy to realize the modification of AuHgPt nanoalloy materials on the surface of ITO glass at room temperature is presented. Gold nanoparticles as templates were obtained by electrochemical deposition, mercury was introduced as an intermediate to form an amalgam, and then a galvanic replacement reaction was utilized to successfully prepare gold–mercury–platinum (AuHgPt) nanoalloys. The obtained alloys were characterized by scanning electron microscopy, UV–Vis spectroscopy, X-ray photoelectron spectroscopy and X-ray diffraction techniques. The electrochemical sensing performance of the AuHgPt-modified electrode for hydrogen peroxide was evaluated by cyclic voltammetry and chronoamperometry. Under light conditions, the AuHgPt-modified electrode exhibited a desirable current response in the detection of hydrogen peroxide due to the synergistic effect of the localized surface plasmon resonance effect inherent in gold nanoparticles, and this synergistic effect improved the sensitivity of hydrogen peroxide detection. Meanwhile, the AuHgPt-modified electrode also exhibited better stability and reproducibility, which makes the modified electrode have great potential for various applications in the field of electrochemical sensing.